(untitled) (Revista Direito em Debate, 2020)
This study studies the parceling and free assignment of Sunday soil surface for housing purposes as a private legal instrument of land regularization in APAs collaborating with the State, inherited from the result of mistaken and immediate urban policies, in this sense. The method used was the literature review and integrated analysis of the relevant legislation, exploring the social, environmental and economic perspectives. The Ministry of the Environment states that despite the existence of appropriate laws and instruments, the current stage of implementation of environmental and urban public policies does not meet the necessary sustainability requirements and should use all available legal instruments to harmonize fundamental housing rights, balanced environment and the consequent economic development. We pursue the idea that it is not enough to donate or subsidize housing, requiring compensation from the beneficiary population to fulfill their citizen role by participating in environmental education programs as an accidental clause of the contract, exercising possession with environmental awareness in its use. Thus, the State is required to develop a strategic environmental assessment, which includes the use of all legal instruments capable of providing sustainable urban development, including the specific contract object of the text.